Development of Plastic Shredder Technology to Support Plastic Waste Reduction - Harjuma, Harjuma; Tahir, Abdul; Sirama, Sirama; Aswar, Aswar (International Journal of Engineering, Science and Information Technology, 2025)
The plastic waste problem in Indonesia has reached a severe level. Data from the National Waste Management Information System shows that Indonesia produces around 17 million tons of plastic waste yearly. However, only approximately 66.47% of this plastic waste undergoes recycling, with the remainder ending up in landfills or polluting the sea. This condition places Indonesia in second place in the world after China in terms of the amount of plastic waste produced, making it a country with a plastic waste emergency. This article discusses the development of plastic recycling machine technology as a solution to overcome the plastic waste problem in Indonesia. With a production of around 17 million tons of plastic waste per year, Indonesia faces significant challenges in plastic waste management. Low efficiency often constrains the effectiveness of plastic recycling as a solution. Therefore, this study aims to design and improve the efficiency of a plastic shredder machine. This machine uses specially designed rotating blade technology to produce high-precision plastic flakes. Additionally, we have updated the transmission system to reduce vibration and implemented other innovations to enhance the machine's capacity to shred various types of plastic. We expect this machine to decrease greenhouse gas emissions from the recycling process and lower operational costs. This study shows that the developed plastic shredder machine can work effectively and efficiently, meeting the research objectives of producing plastic flakes quickly. Thus, we expect this machine to significantly reduce plastic waste in Indonesia and support environmental conservation efforts.